2001
DOI: 10.3201/eid0703.010325
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Phage Associated with Recent Pandemic Strains ofVibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus, a halophilic gram-negative rod, causes seafood-borne gastroenteritis in humans. Infections caused by this organism have been associated with diverse serovars: 13 O serotypes and 75 K serotypes have been identified. Recent studies, however, have revealed the emergence and pandemic spread of a single serovar, O3:K6 (1-6). Strains belonging to the O3:K6 serovar abruptly appeared in India in 1996 and have since been isolated in Southeast Asian countries, from travelers at quarantine statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 8 publications
(2 reference statements)
1
52
0
Order By: Relevance
“…Hence, one or more of these vibriophages are also likely to package possible other DNA elements carrying the appropriate signals, and thus we speculate that the range of DNA transfer mediated by filamentous phages may be considerably more than currently appreciated. In this regard, it is also remarkable that a gene (orf8) associated with a filamentous vibriophage has been linked exclusively to strains associated with the "pandemic" O3:K6 clone of Vibrio parahaemolyticus (22,32).…”
Section: Vol 187 2005mentioning
confidence: 99%
“…Hence, one or more of these vibriophages are also likely to package possible other DNA elements carrying the appropriate signals, and thus we speculate that the range of DNA transfer mediated by filamentous phages may be considerably more than currently appreciated. In this regard, it is also remarkable that a gene (orf8) associated with a filamentous vibriophage has been linked exclusively to strains associated with the "pandemic" O3:K6 clone of Vibrio parahaemolyticus (22,32).…”
Section: Vol 187 2005mentioning
confidence: 99%
“…The results suggest that ORF8 rather than toxRS/new is a more reliable genetic marker for identification of the pandemic strains. However, Iida et al (4) pointed out that one of the O3:K6 strains belonging to the pandemic PFGE type was negative for ORF 8. More recently, Bhuiyan et al (2) reported that eight of the O3:K6 clinical strains isolated between 1998 and 2000 were negative for ORF8, claiming that ORF8 was a poor genetic marker for the pandemic genotype.…”
mentioning
confidence: 99%
“…Matsumoto et al (5) reported that the pandemic strains exhibit a unique sequence within the toxRS operon, which encodes transmembrane proteins in the regulation of virulence-associated genes conserved in the genus Vibrio. On the other hand, Nasu et al (6) isolated filamentous phage possessing a unique open reading frame, ORF8, from one of the pandemic strains, and Iida et al (4) claimed that ORF8 was a useful genetic marker for identifying strains. It was thus necessary to evaluate the use of the toxRS sequence or ORF8 as a reliable genetic marker for the identification.…”
mentioning
confidence: 99%
“…This clonality was also supported by the fact that most of these strains belong to a single "new" serotype O3:K6 (Okuda et al, 1997). Additionally, several PCR analyses identified nucleotide sequences unique to these pandemic strains (Matsumoto et al, 2000;Nasu et al, 2000;Iida et al, 2001;Williams et al, 2004;Okura et al, 2004Okura et al, , 2005. However, where and how these pandemic strains have emerged and how the infection by these strains have spread throughout the world are not known to date.…”
Section: Introductionmentioning
confidence: 99%